Establishing rapport: a visit to China - Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
11-16 Oct 2009- The new CMLHS management team recently set off on a working trip to China to visit the School of Foreign Languages of South Central University for Nationalities (SCUN), Wuhan. Leading the delegation was the newly appointed Dean of CMLHS, Prof. Dr. Abd. Jalil bin Borham, accompanied by the Deputy Dean of Academic Affairs, Munira Abdul Razak, Wan Jumani Fauzi, the Head of Department of Modern Languages and Mohd. lszuani Mohd Hassan, the Head of Department of Foreign Languages.